Assisting, Instructing, Assessing: 21st Century Student Centered Librarianship. Issue 1 (2nd January 2020) - Newton, Lauren; Feinberg, Daniel E.
ABSTRACT: For librarians at the University of North Florida, there was a need to move beyond information literacy instruction to one-on-one and small group research consultations to aid in student success. By staffing the research desk with staff and students, librarians were able to open their calendars to allow more time for in-person, phone, and online consultations to aid in meeting the research goals of students at the institution. After assessing the research consultation program for two years, there has been a positive correlation between research consultation usage, satisfaction in completing assignments, and student success measures throughout the university.